Rancangan Sistem Pembuatan Kapur Tohor di Desa Lakarinta Kabupaten Muna Provinsi Sulawesi Tenggara - LO Ngkoimani; Jahidin Jahidin; Suryawan Asfar (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
The partner in this Community Partnership Program (PKM) was Lakarinta Village community group, especially the youth group who have businesses in making calcium oxide. Problem faced by partner was that so far the making of calcium oxide from burning limestone is done in an open space (influenced by outside air) using wood fuel taken in the surrounding environment. In this way, community group produced calcium oxide takes a long time because the process of burning limestone does not take place optimally due to heating which is heavily influenced by outside air. To overcome the problem of partner, the PKM Community Service Team designed a system of making calcium oxide with the aim of activities, namely : (1) The existence of an effective calcium oxide making system from the burning of limestone which could be used by the community group of youth groups to increase and accelerate the activities of calcium oxide production, (2) Increasing public knowledge about how to make calcium oxide through an effective limestone combustion system so that it can increase and accelerate the production. The method of implementing the activities were: socialization and field survey, the design of the calcium oxide-making system, trials, and discussions / questions and answers with partners. The results achieved were (1) partners have an effective calcium oxide making system (furnace using heating element / heat storage), (2) partners have knowledge in making calcium oxide through an effective limestone combustion system so as to increase and accelerate production activity